Unfinished Paths—From Blockchain to Sustainability in Supply Chains - Köhler, Susanne; Pizzol, Massimo; Sarkis, Joseph (Frontiers in Blockchain, 2021)
Blockchain technology has been promised as a solution to social and environmental issues in supply chains. The potential includes reduction of vulnerable party exploitation and avoiding environmentally harmful practices. Yet, it remains unclear how these potential improvements are created and whether blockchain can truly contribute. Therefore, this field study explores and identifies the mechanisms for blockchain technology to facilitate positive social and environmental impacts in supply chains. We applied an explorative qualitative research approach and interviewed blockchain technology implementers and practitioners that allowed a detailed analysis of this problem despite the scarcity of practice data. The results include the development of a middle-range theory that shows barriers and drivers of blockchain-based technologies in supply chains, introduces the concept of blockchain-enabled system, and outlines expected outcomes and impacts. We further identify four impact pathways that describe how blockchain-enabled system create positive impact: (voluntary) market mechanisms, plausibility checks, smart contracts and tokenisation, and peer-to-peer trust. The study contributes by providing insights into “how” blockchain-based technologies in supply chains can lead to social and environmental impacts. The study also furthers the discussion on blockchain technology’s role in supply chain implementation and addresses the yet unresolved problem of measuring the impact of such blockchain-enabled systems.